2009
DOI: 10.1002/pmic.200800795
|View full text |Cite
|
Sign up to set email alerts
|

Proteome mapping of the Drosophila melanogaster male reproductive system

Abstract: The fruit fly Drosophila melanogaster is an excellent model organism for studying insect reproductive biology. Although the gene expression profiles of both male and female reproductive organs have been studied in detail, their proteomic profiles and functional characteristics largely remained to be clarified. In this study, we conducted proteome mapping of the male internal reproductive organs using 2-DE. We identified a total of 440 protein components from gels of the male reproductive organs (testis, semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 46 publications
3
101
0
Order By: Relevance
“…For example, recent studies identified proteins from male reproductive tissues in flies and mice. (30,31,40) Many of these proteins may interact with female proteins, and others may influence the regulation or modification of interacting proteins. Others, however, could play housekeeping roles that do not relate specifically to reproduction.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent studies identified proteins from male reproductive tissues in flies and mice. (30,31,40) Many of these proteins may interact with female proteins, and others may influence the regulation or modification of interacting proteins. Others, however, could play housekeeping roles that do not relate specifically to reproduction.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
“…A recent explosion of proteomics studies has identified many reproductive proteins in taxa ranging from crickets and honeybees to rodents and humans. (15,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) Applying mass spectrometry (MS)-based proteomics to the study of reproduction has been particularly fruitful, in our view, because reproductive tissues are often specialized cell types with the discrete function of producing proteins involved in a specific biological process. Thus, biochemical isolation and purification of proteins from these tissues and cell types are straightforward, and large amounts of relatively pure protein mixtures can be analyzed by MS.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
“…In D. melanogaster, ablation of the major Sfp-producing tissue, the male accessory gland (AG), results in the complete loss of male fertility (Kalb et al 1993;Gligorov et al 2013), unless Sfps are provided by a second male (Xue and Noll 2000). Over 200 Sfps are transferred (or inferred to be transferred) to females during mating in D. melanogaster (Ravi Ram and Wolfner 2007;Findlay et al 2008Findlay et al , 2009Takemori and Yamamoto 2009;Yamamoto and Takemori 2010). However, functions have been assigned to only a small proportion of Sfps in this, or any, species (Avila et al 2011).…”
mentioning
confidence: 99%
“…In humans, .100 proteins in the seminal plasma are proteolysis regulators (out of 950 seminal proteins) (Utleg et al 2003;Fung et al 2004;Pilch and Mann 2006). In D. melanogaster, proteins with predicted protease or protease inhibitor domains account for at least 14% of known or inferred Sfps (Ravi Ram and Wolfner 2007;Findlay et al 2008Findlay et al , 2009Takemori and Yamamoto 2009;Yamamoto and Takemori 2010), though individual proteins in this class tend to be of low abundance (Findlay et al 2008).…”
mentioning
confidence: 99%
“…Drosophila resources have been maintained in the laboratory for a very long time by inbreeding, and by using balancers and other techniques for producing homozygous populations on any scale. This homozygous constant genetic background is very valuable in proteomic analyses [41,50]. A high frequency of SNPs is convenient for mapping genes, but it causes serious problems in comprehensive proteomic profiling of specific tissues and organs.…”
Section: Human Disease Model Organismmentioning
confidence: 99%